Digital Literacy: Effort to Increase Interest in Reading at SDN Nglumber II Kepohbaru Bojonegoro - Rohmatul Faizah (Future Science, 2022)
The goal of SDN Nglumber II Kepohbaru is to develop students' character by putting the school literacy motion policy into practice. The School Literacy Motion (GLS) is a result of the Minister of Education and Culture's Order No. 23 of 2015, which is focused on